Adolescents' Friends, Parental Social Closure, and Educational Outcomes. Issue 1 (2nd January 2018) - Carolan, Brian V.; Lardier, David T.
ABSTRACT: There is a growing recognition of the importance of the social resources accessed through friends on adolescents' educational outcomes. However, the research on the influence of these social resources remains inconclusive, due primarily to the different ways in which social resources have been conceptualized and measured. Using panel data from the Educational Longitudinal Study, we estimate the association between two measures of adolescents' social resources in the Educational Longitudinal Study base-year, their high school grade point average in the first follow-up, and the likelihood of attaining a four-year college degree by the third follow-up. Grounded in the literature on social capital, our findings show that friendships that provide access to high social closure parental networks are favorably associated with grade point average and college completion. We discuss results in terms of their implications on school reform efforts intended to manufacture adolescents' access to norm-reinforcing networks.